2012
DOI: 10.2151/jmsj.2012-c10
|View full text |Cite
|
Sign up to set email alerts
|

Role of Patchy Snow Cover on the Planetary Boundary Layer Structure during Late Winter Observed in the Central Tibetan Plateau

Abstract: The one-dimensional structure of a daytime planetary boundary layer (PBL) with shallow cloud development was captured by intensive sonde observation during the late winter season at the central Tibetan Plateau (TP), and its relationship to patchy snow cover conditions was revealed. The diurnal change of potential temperature was evident in the atmosphere up to 1 km above ground, indicating PBL development, and frequent cloud formation in the afternoon and night over the PBL was confirmed by the increase of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, the wind blow effect and canopy snow interception, which have been recognized as important to the accurate simulation of snowpack dynamics (Mahat and Tarboton, 2014), are not taken into account in detail. Last but not least, the interpretation of surface albedo dynamics needs to be adapted to the specific site, especially regarding the shallow snow situations (Ueno et al, 2007(Ueno et al, , 2012Ding et al, 2017;Wang et al, 2017). The albedo of the underlying surface should also be properly accommodated to this Tibetan meadow system.…”
Section: Uncertainties In Simulations Of Surface Albedo and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the wind blow effect and canopy snow interception, which have been recognized as important to the accurate simulation of snowpack dynamics (Mahat and Tarboton, 2014), are not taken into account in detail. Last but not least, the interpretation of surface albedo dynamics needs to be adapted to the specific site, especially regarding the shallow snow situations (Ueno et al, 2007(Ueno et al, , 2012Ding et al, 2017;Wang et al, 2017). The albedo of the underlying surface should also be properly accommodated to this Tibetan meadow system.…”
Section: Uncertainties In Simulations Of Surface Albedo and Limitationsmentioning
confidence: 99%
“…Many physically based models for the mass and energy balance in the snowpack have been developed for their coupling with hydrological models or atmospheric models. Boone and Etchevers (2001) divided these snow models into three main categories: (i) simple forcerestore schemes with the snow modeled as the composite snow-soil layer (Pitman et al, 1991;Douville et al, 1995;Yang et al, 1997) or a single explicit snow layer (Verseghy, 1991;Tarboton and Luce, 1996;Slater et al, 1998;Sud and Mocko, 1999;Dutra et al, 2010); (ii) detailed internal snow process schemes with multiple snow layers of fine vertical resolution (Jordan, 1991;Lehning et al, 1999;Vionnet et al, 2012;Leroux and Pomeroy, 2017); and (iii) intermediatecomplexity schemes with physics from the detailed schemes but with a limited number of layers, which are intended for coupling with atmospheric models (e.g., Sun et al, 1999;Boone and Etchevers, 2001). The intercomparison results of the abovementioned snow models at an alpine site indicated that all three types of schemes are capable of representing the basic features of the snow cover over the 2-year period but behaved differently on shorter timescales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the wind blow effect and canopy snow interception, which have been recognized as important to the accurate simulation of snowpack dynamics , are not taken into account in detail. Last but not least, the interpretation of surface albedo dynamics needs to be adapted to the specific site, especially regarding the shallow snow situations (Ueno et al, 2007;Ueno et al, 2012;Ding et al, 2017;Wang et al, 2017b). The albedo of the underlying surface should also be properly accommodated to this Tibetan meadow system.…”
Section: Uncertainties In Simulations Of Surface Albedo and Limitationsmentioning
confidence: 99%